The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
26th Annual Conference of the International Group for Lean Construction 2018
DOI: 10.24928/2018/0520
|View full text |Cite
|
Sign up to set email alerts
|

Using BIM-Based Sheets as a Visual Management Tool for on-Site Instructions: A Case Study

Abstract: In recent decades, design and construction have had to specialize, which has gradually fragmented the industry. This scenario is relevant in hospital projects, where a large number of specialties interact, especially when the operation of the center must be guaranteed. For this reason, it is essential to reduce the communication time between workers and decision-makers to respond quickly to unexpected problems. The purpose of this article is to describe the use of Visual Management using Building Information M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The nationality of these authors is concentrated in twenty-two countries as shown in table 1. However, the most representative countries are Germany (Dlouhy, et al, 2017), Brazil (Franco and Picchi, 2016), Chile (Salvatierra, et al, 2015;Matta, et al, 2018), United States (Smith and Ngo, 2017;Alves, Azambuja and Arnous, 2016), India (Patel, Karia and Pandit, 2018), England (Tezel, et al, 2016) and Norway (Torp, Knudsen and Ronneberg, 2018). Other authors consulted came from Australia (Shou, et al, 2017), Ecuador (Martínes, Tommelein and Alvear, 2017), Estonia (Leonova, Ballard and Gehbauer, 2017), Finland (Singh, 2018), Ireland (Kemmer, et al, 2016), Lebanon (Hatoum, et al, 2018), Morocco (Hicham, Taoufiq and Aziz, 2016), Mexico (Dlouhy, et al, 2018), New Zealand (Hunt and Gonzalez, 2018), Netherlands (Vrijhoef, Dijkstra and Koutamanis, 2018), Peru (Murguía, Brioso and Pimentel, 2016), Palestine (Enshassi and Abu Zaiter, 2014), South Africa (Monyane, Emuze and Crafford, 2018) and Pakistan (Memon, et al, 2018).…”
Section: Search For Expertsmentioning
confidence: 99%
“…The nationality of these authors is concentrated in twenty-two countries as shown in table 1. However, the most representative countries are Germany (Dlouhy, et al, 2017), Brazil (Franco and Picchi, 2016), Chile (Salvatierra, et al, 2015;Matta, et al, 2018), United States (Smith and Ngo, 2017;Alves, Azambuja and Arnous, 2016), India (Patel, Karia and Pandit, 2018), England (Tezel, et al, 2016) and Norway (Torp, Knudsen and Ronneberg, 2018). Other authors consulted came from Australia (Shou, et al, 2017), Ecuador (Martínes, Tommelein and Alvear, 2017), Estonia (Leonova, Ballard and Gehbauer, 2017), Finland (Singh, 2018), Ireland (Kemmer, et al, 2016), Lebanon (Hatoum, et al, 2018), Morocco (Hicham, Taoufiq and Aziz, 2016), Mexico (Dlouhy, et al, 2018), New Zealand (Hunt and Gonzalez, 2018), Netherlands (Vrijhoef, Dijkstra and Koutamanis, 2018), Peru (Murguía, Brioso and Pimentel, 2016), Palestine (Enshassi and Abu Zaiter, 2014), South Africa (Monyane, Emuze and Crafford, 2018) and Pakistan (Memon, et al, 2018).…”
Section: Search For Expertsmentioning
confidence: 99%
“…However, usually 4D BIM models are used for pre-construction planning and not for managing the execution process. Matta et al (2018) describe the use of BIM-based sheets as a visual management tool to provide task instructions to the field. The approach was applied to a Chilean hospital construction project and the achieved results were the fulfilment of deadlines thanks to a reduction of response times for information requests.…”
Section: Related Workmentioning
confidence: 99%
“…The approach was applied to a Chilean hospital construction project and the achieved results were the fulfilment of deadlines thanks to a reduction of response times for information requests. However, the authors point out that simply applying the technology is not enough, but it is essential to use it within a Lean collaborative methodology (Matta et al 2018). Bhatla and Leite (2012) described the advantages of using BIM on-site, to provide documentation and information for the work teams about products and process activities, with a 3D/4D components visualization.…”
Section: Related Workmentioning
confidence: 99%
“…While some of this can be seen in the matrix proposed by Sacks et al (2010), this study is limited to an analysis of the literature focused on Lean principles, not practices. Additionally, there are empirical studies that provide evidence of the potential of the application of BIM and Lean (Gerber et al 2010;Matta et al 2018;Schimanski et al 2019); however, these are limited to the application of particular Lean tools and BIM uses in a limited number of case studies. Hence, a comprehensive understanding of BIM/Lean management is needed.…”
Section: Introductionmentioning
confidence: 99%